Analisis tingkat kepatuhan wajib pajak orang pribadi dalam pelaporan SPT Tahunan melalui sistem e-filing selama masa pandemi COVID-19 di Kantor Pelayanan Pajak Pratama Manado - Imbang, Theafilia Viona; Walandouw, Stanley Kho; Weku , Priscillia (Yayasan Widyantara Nawasena Raharja, 2024)
E-filing is an annual tax return in the form of an electronic form, and its delivery is done in the format of digital data. The purpose of this research is to determine the level of compliance of individual taxpayers in reporting annual tax returns through the e-Filing system during the COVID-19 pandemic, and to determine the constraints and efforts to improve taxpayer compliance. The research method used is descriptive qualitative and descriptive quantitative, for data obtained from the results of documentation and interviews. The results of this research is so many taxpayers have used e-Filing because of its practicality, more spesifically also because of the implementation of a social distancing system which aims to avoid direct contact with tax officials. KPP Pratama Manado also continues to provide education and socialization through social media platforms to taxpayers who still do not understand the e-Filing system.